Penguatan Manejemen dan Budidaya Sayuran Secara Hidroponik di Dayah Al Huda Malikussaleh - Nasruddin Nasruddin; Muhammad Nazaruddin; Khusrizal Khusrizal (Forum Kerjasama Pendidikan Tinggi, 2021)
The traditional dayah or dayah salafi is a dayah built by the community or a dayah leader personally, only teach Islamic sharia education and do not teach general education. In traditional dayah, teachers/teungku and students do not get management knowledge and skills. In managing dayah and earning income to support themselves and their families, it is often an obstacle for them. This community service is carried out aimed at strengthening traditional dayah management so that it becomes a well-managed dayah and introduces / practices hydroponic vegetable cultivation to increase its income. This method of implementing community service is carried out by providing theories about management, hydroponics and direct practice by providing materials, tools and building screen houses. The results of the implementation of community service achieved are that teachers/teungku and students have understood management and can master hydroponic cultivation of vegetables. This training can develop dayah management and have skills in hydroponic vegetable cultivation